Dyspepsia in Cirrhotic Hepatitis C Patients - Maryam Jalil, Faiza Aslam, Talal Khurshid Bhatti, Muhammad Umar, Hamamatul Bushra Khaar (Journal of Rawalpindi Medical College, 2017)
Abstract Background:To determine the frequency of patients with dyspepsia, its patterns of presentation and causes along with their associations with gender and age, amongst HCV cirrhotic patients presenting to a tertiary care health facility of Rawalpindi. Methods: In this cross sectional study 207 HCV cirrhotic patients,above 25 years of age irrespective of gender, were included. Patients receiving prolonged treatment of acid suppression prior to hospitalization were excluded. After taking history and performing thorough physical examination, routine laboratory investigations, abdominal ultrasonography and endoscopies were performed to determine the cause of dyspepsia. Results:Amongst 207 HCV cirrhotic patients 146 (70.5%) were presented with dyspepsia. Pain in epigastrium 92 (63.0%), heart burn 81 (55.5%) and water brash 65 (44.5%) were most common patterns of presentation of dyspepsia in HCV cirrhotic patients.Portal hypertensive gastropathy 77(52.7%) came out as leading etiology of dyspepsia, followed by gastritis 9(6.2%), ulcer 6(4.1%) and cholelithiasis4(2.7%). Amongst those diagnosed with Dyspepsia, 25(17.1%) patients were found to have functional dyspepsia i.e. no organic cause was found. Conclusion:Dyspepsia is very frequent phenomenon in HCV cirrhotic patients with most common patterns of presentation as pain in epigastrium and heart burn. The leading cause of dyspepsia was portal hypertensive gastropathy.